sBotics - Gamified Framework for Educational Robotics - Nascimento, Lucas Moura do; Neri, Davi Souto; Ferreira, Thiago do Nascimento; Pereira, Francinaldo de Almeida; Albuquerque, Erika Akemi Yanaguibashi; Gonçalves, Luiz Marcos Garcia; Sá, Sarah Thomaz de Lima (Journal of intelligent & robotic systems, 2021)
This paper proposes a learning framework for Educational Robotics named sBotics, which includes a complete environment for teaching and programming skills acquisition designed for both teachers and K-12 students. Our framework has been developed using a gamified approach with the system and simulated environment developed in the Unity game engine. The main novelty of this platform is its ease-of-use combined with the flexibility to create a variety of scenarios with endless learning potential, in contrast to our evaluations where no alternatives with such characteristics were found for the K-12 range that we are targeting. Also as a contribution of our proposal, robot programs are treated as games that are affected by a disturbance model, which acts in the robotic system and environment variables. This model is introduced in order to approximate what happens in a real robot programming platform. Besides, it is possible for the user, throughout its use, to code in three levels of abstraction: its overly intuitive native programming language called R-Educ, BlockEduc (R-Educ version of Blockly), and C#. Programs can be compiled and interpreted by virtual robots executing any given command. As for teachers, the framework API offers tools that can be employed in the assembly and customization of the learning setup. The whole platform has been built as a tool dedicated to spreading the worlds of Robotics and Programming among youngsters, as well as making them more affordable to everyone. It has been validated by our experiments and is currently being used during the novel Coronavirus pandemic by the official RoboCupJunior Rescue trials in Brazil, currently with more than a thousand competing teams (about 5 thousands students).